THE SEVERAL UNLAWFUL ACT AFTER NUPTIAL AGREEMENT IN INDONESIA - Heriyanti, Heriyanti; Pakpahan, Elvira Fitriyani; Diana, Diana (UNISSULA, 2021)
The rule of Constitutional Court has eased on the essential interpretation inherent in the prevailing prenuptial agreement. The prenuptial agreement is understood no longer as the one drawn up prior to the marital process but thereafter as well, as long as it is not against the norms of religion, public order, morals, and third parties. Essentially, it is in accordance Act on Marriage and seemingly more comprehensive than the interpretation of marital agreement of inherence at civil law. The approach method used is a normative juridical approach, the research results obtained state that the implication that the marital agreement can be drawn up either after or before the nuptial execution. The nuptial agreement is compulsory to be legalized on the notarial deed before the execution. The nuptial agreement before or at the moment of marital execution process under the terms that it does no harm to the third part